Optical Property of Polarization-Maintaining Fiber Taper for Tunable Multi-Wavelength Fiber Laser Generation - Feng Yuan; Jinjin Zhao; Weifeng Jiang; Hongdan Wan (IEEE Photonics Journal, 2020)
We investigate optical property of polarization-maintaining fiber taper (PMFT) for tunable multi-wavelength laser generation in a fiber ring cavity. A panda-type polarization fiber is fused and tapered into a fiber taper with a diameter of about 2.5 μm. Optical and thermal properties of the PMFT are investigated theoretically and experimentally. As combined with a polarization dependent isolator, tunable multi-wavelength fiber laser operation is achieved by controlling of polarization-dependent loss in the fiber ring cavity. The laser wavelength number can be switched from 1 to 4. The 3 dB bandwidths of laser spectra are less than 0.05 nm for all wavelength numbers, with a maximum OSNR of about 54 dB. For single-wavelength laser operation near 1561.66 nm, the measured wavelength and power fluctuations are < 0.02 nm and 0.4 dB, respectively.